Plandemic Revisited: A Product of Planned Disinformation Amplifying the COVID-19 “infodemic” - Nazar, Shahin; Pieters, Toine (Frontiers in Public Health, 2021)
During the first few months of the COVID-19 pandemic, a 26-minute documentary entitled Plandemic was released online and fanatically shared via Twitter and other major social media platforms. The producers of the documentary sought to spread misinformation and conspiracy theories and to discredit scientific experts using a sophisticated disinformation campaign. They set out to accomplish this by coaching citizens towards activism to maximize the speed at which the documentary propagated and decrease positive sentiments towards public health interventions. Applying techniques from Social Network Analysis in conjunction with formative content analysis of Twitter data, the present study examined the effectiveness of the Plandemic disinformation campaign as a case study of social engineering during the COVID-19 pandemic. By comparing the Twitter network’s community structure and communication patterns before and after the release of the film, we demonstrate the Plandemic campaign to have been effective for two reasons. First, the campaign established a decentralized information sharing network on Twitter by coaching low-reach social media users to mass share the documentary, effectively subverting efforts to gatekeep its misinformation. Second, the campaign amplified negative sentiments regarding vaccination and containment measures, at least temporarily diminishing public willingness to comply with public health measures. Our results show the necessity of further research on sophisticated social experiments such as the Plandemic disinformation campaign and provide important insights for policy-making to combat the spread of health misinformation during public health crises.